Crumpled graphene balls adsorb micropollutants from water selectively and rapidly. (15th October 2021) - Fu, Han; Huang, Jiaxing; Gray, Kimberly
Abstract: Thousands of anthropogenic materials (e.g., micropollutants, MPs) are discharged to surface and groundwaters daily and their wide distribution potentially threatens ecological and human health. Granular activated carbon (GAC) is a widely used adsorbent to remove MPs, but with several deficiencies such as slow adsorption kinetics and hindered performance by natural organic macromolecules (NOM). Here, we detail the synthesis of a novel adsorbent, three-dimensional (3D), stacking-resistant, crumpled graphene oxide balls (CGBs) and their adsorbent properties by using eight persistent MPs under relevant environmental conditions. CGBs displayed 4–8 times greater adsorption capacity than GAC for seven of the eight MPs on a surface area equivalent basis. Kinetic experiments show that seven of eight MPs in a mixture reach >90 % removal efficiency after 15 min contact time (compared to 5–10 % removal of GAC). CGB adsorption performance was also tested as a function of varying NOM concentration, with other realistic environmental conditions of pH, ionic strength, water hardness, and alkalinity, to demonstrate that CGB adsorption of MPs is not adversely affected by NOM even at high concentrations and is stable over a range of field conditions. These findings demonstrate that CGBs are potentially a powerful adsorbent for micropollutant removal in complex aqueous environments. Graphical abstract: Image 1